A liberdade do indivíduo e o bem estar social em John Stuart Mill - Kurmann, Daniel (My University, 2025)
This dissertation investigates the relationship between individual liberty and social well-being through the lens of John Stuart Mill's thought. Based on a qualitative and analytical approach to Mill's works, it explores the main ethical and political foundations of Millian philosophy, highlighting his reformulation of classical utilitarianism, the principle of liberty, and his critique of the tyranny of the majority. The study argues that individual freedom-understood as non-interference and personal sovereignty-is an essential condition for the moral and intellectual development of citizens, as well as for the construction of a just and pluralistic society. It also examines the tension between autonomy and social authority, articulating the harm principle as a normative criterion for legitimate state intervention. Finally, it contrasts Mill's thought with the analyses of James Fitzjames Stephen and Isaiah Berlin, shedding light on the challenges and potentialities of his proposal in democratic contexts. In this sense, the dissertation aims to investigate the foundations of Mill's thought in light of his intellectual background and historical context, to analyze the principle of utility with special attention to the introduction of the quality of pleasures as a moral criterion, to discuss the principle of liberty-especially the concept of individual sovereignty and the role of the state-and to interpret the harm principle as an attempt to establish the legitimate limits of social intervention in the private sphere. [resumo fornecido pelo autor]
Esta dissertação investiga a relação entre a liberdade do indivíduo e o bem-estar social a partir do pensamento de John Stuart Mill. Com base em uma abordagem qualitativa e analítica das obras de Mill, a dissertação investiga os principais fundamentos éticos e políticos da filosofia milliana, destacando sua reformulação do utilitarismo clássico, o princípio da liberdade e a crítica à tirania da maioria. O trabalho sustenta que a liberdade individual, compreendida como não interferência e soberania pessoal, é condição indispensável para o desenvolvimento moral e intelectual dos cidadãos, bem como para a construção de uma sociedade justa e plural. Examina-se, ainda, a tensão entre autonomia e autoridade social, articulando o princípio do dano como critério normativo para a intervenção legítima do Estado. Por fim, confronta-se o pensamento de Mill com análises de James Fitzjames Stephen e Isaiah Berlin, evidenciando os desafios e potencialidades de sua proposta em contextos democráticos. Nesse sentido, a dissertação busca investigar os fundamentos do pensamento milliano à luz de sua formação intelectual e contexto histórico; analisar o princípio da utilidade, com especial atenção à introdução da qualidade dos prazeres como critério moral; discutir o princípio da liberdade, especialmente o conceito de soberania individual e o papel do Estado; e interpretar o princípio do dano como tentativa de estabelecer os limites legítimos da intervenção social na esfera privada. [resumo fornecido pelo autor]
Keywords: Mill, John Stuart, 1806-1873; Liberdade - Filosofia; Bem-estar social; Utilitarismo; Democracia; Liberty - Philosophy; Public welfare; Utilitarianism; Democracy